Family supported nomophobia reduction intervention for adolescents - Berber Çelik, Çiğdem; Küçük, Ahmet Rıdvan; Kulaberoğlu, Neslihan (Journal of Dependence, 2024)
Objective: The aim of this study is to test the effectiveness of the family-supported nomophobia reduction psychoeducation program developed for adolescents on the level of nomophobia. Method: A total of 24 high school students, 12 of which were in the experimental group and 12 in the control group, participated in the study, which was designed according to the quasi-experimental design. Personal Information Form and Nomophobia Scale were applied to the participants. A training program consisting of 8 sessions of interventions to reduce nomophobia was applied to the experimental group. The families of the students in the experimental group were given a 2-session training on conscious use of technology. No intervention was made in the control group. Results: Group*measurement joint effect examining whether the difference between the mean scores of the pre-test, post-test and follow-up test susceptibility scores for nomophobia of the experimental and control groups differed. The fact that the joint effect is significant indicates that the family-supported nomophobia reduction program was effective in reducing the nomophobia levels of the participants in the experimental group. Conclusion: The intervention program developed against the negative effects of technology will create positive results at a time when the use of technology is increasing day by day.